MILK FORMULAS: PRESENT DAY INFORMATION AND RECOMMENDATIONS - Laura Florescu; Oana-RalucaTemneanu; Dana-Teodora Anton Păduraru; Dana Elena Mîndru (Amaltea Medical Publishing House, 2017)
A healthy child passes through a process of growth and harmonious development, his environment and food quality representing determining premises of his health, especially during the first two years. When breastfeeding is impossible due to the absence of milk secretion installation or to an insufficient amount of maternal milk, the alternative sources of feeding consist either in the administration of milk formulas or, under precarious social-economical conditions, in cow milk. As each infant has its individual needs, there is a variety of milk formulas, such that to provide the infant an adequate quantitative and qualitative nutrition, optimum for a harmonious development. There are several categories of formulas, based on proteins from milk or soy, hydrolyzed proteins and amino acids, as well as differences between the products from each category.